O ekonomiji gašenja požara raslinja iz zraka na primjeru Canadair CL-415 - Regent, Aleksandar (Array, 2018)
Innovations introduced in firefighting practice should help maximise the cost/benefit relation. One of the largest costs of firefighting in Croatia is the cost of aerial firefighting. The majority of the costs are incurred by the procurement, maintenance and actual operation of the hydroplane Bombardier CL-415. Published data indicate that these costs are significantly underestimated in Croatia. The paper purports to show the actual costs of wildfire fighting using these planes. An additional cost, if class A foam is used, amounts to 12-13% of total costs. One of the conclusions is that in order to increase the total efficiency of fire extinguishing and cut the cost would be to use Class A foam, since the extra cost is, most likely, significantly smaller than the proven advantages of this agent.